The Impact of Depopulation on the Sustainability of Local Businesses in Yoshinogawa, Japan - Liwan Karamina, Tijani; Nabila Puti Aura, Shalsa; Tafdila Aulia Magfiroh, Nadia; Afaaf Fauziyya Dewicaksana, Lintang; Ciha Widya Dewati, Talita; Putri Amelia, Dwi (LPPM Universitas Harapan Bangsa, 2025)
Depopulation and demographic aging present critical threats to rural economies in Japan, particularly in municipalities like Yoshinogawa where small businesses struggle to sustain operations within a shrinking consumer base. This study investigates the resilience of local businesses using a mixed-methods approach that integrates quantitative data from household surveys (n=100) with qualitative insights gathered from interviews, field observations, and case studies. Descriptive statistics were applied to examine consumer behavior, while thematic coding was employed to analyze adaptive business strategies and patterns of community engagement. The results reveal that local business survival depends not on technological innovation or economic expansion but on strong social embeddedness, especially among elderly consumers who act as both vulnerable clients and stabilizing actors through consistent patronage and emotional loyalty. Shopkeepers have responded with micro-level adaptations such as reducing operating hours, offering elderly-friendly services, and transforming their premises into multifunctional community hubs. Despite these efforts, structural challenges including the lack of generational succession, digital exclusion, and limited access to policy support continue to threaten long-term viability. The findings suggest that place-based policy interventions that leverage social capital, promote intergenerational collaboration, and support embedded innovation are essential to sustain economic activity in depopulated areas. The case of Yoshinogawa provides a counter-narrative to prevailing assumptions about rural decline by demonstrating how resilience can emerge from community cohesion and relational infrastructure.